The influence of unverified news and electronic word-of-mouth on customer satisfaction and purchase intention: An empirical study on the food and beverage industry - Ngoc-Hong Duong; Chi Viet Duong; Thien Kim Nguyen Ba; Bao Tran Tran; Minh Chau Thai (Innovative Marketing)
In the digital age, unverified news and electronic word-of-mouth (e-WOM) have become pervasive, raising concerns about their influence on customer behavior and decision-making. This research aims to investigate how unverified news affects customer purchase intention and satisfaction, emphasizing the mediating role of brand image within customer relationship management. Using the Elaboration Likelihood Model (ELM) as the theoretical framework, the study collected the data from 378 undergraduate and postgraduate students in Vietnam. The hypotheses were tested through Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS4. There are two significant results. Firstly, unverified news has significantly influenced brand image and trust, leading to customer satisfaction and purchase intention. Secondly, brand image plays a mediating role in the relationship between e-WOM and purchase intention. This research contributes to the marketing literature by demonstrating how unverified news shapes consumer behavior. The findings provide actionable insights for businesses to adapt their marketing strategies, addressing the growing challenges of misinformation to improve brand trust and customer satisfaction in today’s information-driven market.